PERAN PEMIMPIN DALAM MENINGKATKAN DISIPLIN ANGGOTA POLISI DI LINGKUNGAN SATUAN BRIGADE MOBILKEPOLISIAN DAERAH KALIMANTAN BARAT - Hartono E.21108068?, Rudi (FISIP Universitas Tanjungpura, 2013)
The title of this essay is based on the many issues raised surrounding the enforcement of discipline and improvement of police in the Police Mobile Brigade Unit ofÂ West Kalimantan. It can be seen from the Internal Affairs Unit reports Police Brigade Unit of West Kalimantan in 2011. From these reports it is clear that there are four (4) types of violations of discipline with 32 (thirty two) the number of offenses committed by members of the Police Mobile Brigade Unit of West Kalimantan in 2011.The conclusion of this study is the role of leadership in motivating subordinates to enforce discipline members of the Police Mobile Brigade Unit ofÂ West Kalimantan with: (1) physiological needs, safety, social, esteem, and self-actualization needs, (2) providing a boost, both positive or negative in nature, and (3) providing incentives for members of the Police Mobile Brigade Unit of West Kalimantan have been implemented catered for, although there are still some shortcomings, such as lack of awareness for the potential of self and not get overtime pay and bonuses . To that end, this study recommendations are: (1) the need for awareness efforts to capitalize on every opportunity, (2) create a situation and a positive atmosphere of competition performance. In addition, (3) disciplinary agency that have formed should be further enhanced and is expected to further motivate the parts and / or other units that discipline needs to be improved.Â Keywords: Role of Leader, Motivation, Work Discipline.